Structurally Dependent Electrochemical Properties of Ultrafine Superparamagnetic ‘Core/Shell’ γ-Fe2O3/Defective α-Fe2O3 Composites in Hybrid Supercapacitors - Oleg Bazaluk (MDPI AG, 2021)
The paper presents a method for obtaining electrochemically active ultrafine composites of iron oxides, superparamagnetic ‘core/shell’ γ-Fe2O3/defective α-Fe2O3, which involved modifying sol-gel citrate synthesis, hydrothermal treatment of the formed sol, and subsequent annealing of materials in the air. The synthesized materials’ phase composition, magnetic microstructure, and structural, morphological characteristics have been determined via X-ray analysis, Mossbauer spectroscopy, scanning electron microscopy (SEM), and adsorption porometry. The mechanisms of phase stability were analyzed, and the model was suggested as FeOOH → γ-Fe2O3 → α-Fe2O3. It was found that the presence of chelating agents in hydrothermal synthesis encapsulated the nucleus of the new phase in the reactor and interfered with the direct processes of recrystallization of the structure with the subsequent formation of the α-Fe2O3 crystalline phase. Additionally, the conductive properties of the synthesized materials were determined by impedance spectroscopy. The electrochemical activity of the synthesized materials was evaluated by the method of cyclic voltammetry using a three-electrode cell in a 3.5 M aqueous solution of KOH. For the ultrafine superparamagnetic ‘core/shell’ γ-Fe2O3/defective α-Fe2O composite with defective hematite structure and the presence of ultra-dispersed maghemite with particles in the superparamagnetic state was fixed increased electrochemical activity, and specific discharge capacity of the material is 177 F/g with a Coulomb efficiency of 85%. The prototypes of hybrid supercapacitor with work electrodes based on ultrafine composites superparamagnetic ‘core/shell’ γ-Fe2O3/defective α-Fe2O3 have a specific discharge capacity of 124 F/g with a Coulomb efficiency of 93% for current 10 mA.